Publicistic Discourse: A Cognitive-Axiological Interaction - Demyanova, Yuliya; Abisheva, Vera; Mazhitayeva, Shara; Tapanova, Saule; Toleubaeva, Kamshat; Zhazira, Yerkin (Opción, 2019)
Purpose of the article: to show the mechanisms of interaction between cognitive and axiological components and the methods of communication in the verbal and mental process on the example of the Kazakhstan publicistic discourse. Scientific and methodological basis which has a complex, interdisciplinary character, is made up of the fundamental works of both domestic (R.A. Nurtazina) and foreign (T.A. van Dijk, D. Schiffrin, E.S. Kubryakova, A.A. Kibrik and others) scientists in the field of research discourse. Methods of comparative, functional and stylistic, conceptual analysis of publications of Kazakhstani newspapers on the subject were used at different stages of the research. In the process of working with the text, methods and techniques of facts observation, their typological generalization, etc. were used. This method of work has helped to establish that the changes of the situation in publicistic discourse are dynamic, as they are related to the functional interaction of the subjects engaged in active influential activities. The method has also contributed to the consideration of three mutually determined spheres of activity: cognitive-functional, value-semantic, emotional-evaluative. The axiological context of the discourse as a set of innovative ideas and assessments is recreated in the mind of the individual as a result of actualization of cognitive experience and is due to the actualization of ideological, intellectual and aesthetic values in the mind of the addressee. It is noted that discursive activity provides the implementation of a number of cognitive-axiological capabilities and abilities of the addresser. The research made it possible to understand the process of language functioning, as a means of reflecting thinking processes, and to determine communicative perspectives. Conclusions and recommendations can be used in the courses “Journalism Skills”, “Publicist Skills ”, the elective course on the theory of journalistic discourse, as well as for scientific and educational purposes. The journalistic texts of Kazakhstan "qualitative press" have been analyzed. The language means used to emphasize the dominants of the discourse have been revealed. The examples of the use of social-evaluative vocabulary in Kazakhstan periodicals have been given.